Fast and slow releasing sulphide donors engender distinct transcriptomic alterations in Atlantic salmon hepatocytes - Lazado, Carlo C.; Voldvik, Vibeke; Timmerhaus, Gerrit; Andersen, Øivind (Aquatic Toxicology, 2023)
publishedVersion